2009
DOI: 10.1152/ajpendo.90772.2008
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyecdysone decreases weight and hyperglycemia in a diet-induced obesity mice model

Abstract: The steroid hormone 20-hydroxyecdysone (20HE) is an essential signaling molecule that modulates molting response in insects and may function as a putative anabolic factor in vertebrate animals, although no mammalian 20HE receptor has been identified. Here we show that in H4IIE cell culture, 20HE treatment decreased expression of phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), reduced glucose production, and induced Akt2 phosphorylation sensitive to the phosphoinositide-3 kinase pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 33 publications
8
82
0
6
Order By: Relevance
“…To demonstrate that the HFHC diet did have an effect on body weight in our Ins2Cre:Znt8loxP/loxP mice, we compared the weight gain of our mice to previous studies examining control mice fed a normal chow diet. A previous study showed that 19-wk-old C57Bl/6J mice fed a chow diet had gained on average 21% of their original 6-wk-old body weight (27). By comparison, our 19-wk-old Ins2Cre and Ins2Cre:Znt8loxP/loxP mice fed the HFHC diet gained 84 and 73% of their 6-wk-old body weight, respectively.…”
Section: Cre-:znt8mentioning
confidence: 48%
“…To demonstrate that the HFHC diet did have an effect on body weight in our Ins2Cre:Znt8loxP/loxP mice, we compared the weight gain of our mice to previous studies examining control mice fed a normal chow diet. A previous study showed that 19-wk-old C57Bl/6J mice fed a chow diet had gained on average 21% of their original 6-wk-old body weight (27). By comparison, our 19-wk-old Ins2Cre and Ins2Cre:Znt8loxP/loxP mice fed the HFHC diet gained 84 and 73% of their 6-wk-old body weight, respectively.…”
Section: Cre-:znt8mentioning
confidence: 48%
“…Indeed, much as seen with Nos up-regulation, ecdysone supplementation in vertebrates results in decreased appetite, cholesterol synthesis, and weight gain, while at the same time increasing muscle mass and endurance (Lafont and Dinan 2003;Dinan and Lafont 2006;Kizelsztein et al 2009). Given these apparent abilities to switch fat cell activity from lipid storage to lipid mobilization, a better understanding of the signals and mechanisms underlying NO and ecdysone-mediated effects should provide new insights and possible uses in metabolism based disorders.…”
Section: Nonautonomous Actions On Lipid Metabolismmentioning
confidence: 99%
“…Similarly to HB, 20HE had no effect on food consumption in this model (21). Taken together, these data suggest that plant brassinosteroids and ecdysteroids have similar effects on glucose metabolism and insulin sensitivity in animals; however, the underlying molecular mechanisms and targets may be different.…”
Section: Discussionmentioning
confidence: 62%
“…Whereas animal steroid hormones act through the nuclear receptor family of transcription factors, plant brassinosteroids signal through a cell surface receptor kinase-mediated signal transduction pathway (29,34). At the same time, brassinosteroids share some similarities with ecdysteroids that have a wide array of physiological and pharmacological effects in animals and insects (4), including modulation of protein synthesis (14) and carbohydrate metabolism (21).…”
Section: Discussionmentioning
confidence: 99%